1936
DOI: 10.1152/ajplegacy.1936.116.3.577
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anesthetics on Action Potentials in the Cerebral Cortex of the Cat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1936
1936
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(58 citation statements)
references
References 0 publications
3
55
0
Order By: Relevance
“…Previous investigations into the effects of anaesthetic agents upon the cerebral response to peripheral stimulation have been inconclusive; some authors (Derbyshire, Rempel Forbes & Lambert, 1936;French, Verzeano & Magoun, 1953;Lader & Norris, 1968) reported little or no effect whilst others (Brazier, 1953;Dawson, Podachin & Schatz, 1963;Domino, Corsen & Sweet, 1963;Angel, 1967;Angel et al, 1973;, showed a definite alteration of the cerebral evoked response in a variety of animal species including man. The present investigation shows that all of the commonly used anaesthetic agents, which were tested, produced a consistent alteration in the cerebral evoked response to forepaw stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into the effects of anaesthetic agents upon the cerebral response to peripheral stimulation have been inconclusive; some authors (Derbyshire, Rempel Forbes & Lambert, 1936;French, Verzeano & Magoun, 1953;Lader & Norris, 1968) reported little or no effect whilst others (Brazier, 1953;Dawson, Podachin & Schatz, 1963;Domino, Corsen & Sweet, 1963;Angel, 1967;Angel et al, 1973;, showed a definite alteration of the cerebral evoked response in a variety of animal species including man. The present investigation shows that all of the commonly used anaesthetic agents, which were tested, produced a consistent alteration in the cerebral evoked response to forepaw stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal a possible unilateral trigger for bilateral spike-wave activity, a methohexital (MHXT) infusion (60 mg/min until silent EEG) was given to two patients to suppress all neural transmission except that occurring along thalamocortical and transcallosal connections (11,21), To identify the side of the primary epileptic focus, delays were measured between the first 10-20 post-suppression right-and left-hemisphere spikes at their first detectable positive or negative peak.…”
Section: Barbiturate Suppression Testsmentioning
confidence: 99%
“…MHXT reduces polysynaptic activity (21) and simplifies the EEG pattern. Absence of convexial signals reduces the complexity of MEG spikes, which, similar to MHXT, may reflect the basic spread patterns of LKS spikes better than nonpharmacologic sleep EEG.…”
Section: Source Dynamicsmentioning
confidence: 99%
“…A great deal is already known about the electrical activity of the various regions of the cortex which receive messages from the sense organs: the reactions of the visual area have been analysed in detail by Bartley & Bishop [1933], those of the auditory area in the cat by Bremer [1938] and of the sensory area in the monkey by Marshall, Woolsey & Bard [Bard, 1938], and general surveys have been made by Kornmiiller [1937], by Gerard, Marshall & Saul [1936] and Derbyshire, Rempel, Forbes & Lambert [1936]. Much of the present work has merely confirmed what has been done already, but the recording of nerve impulses as well as cortical potentials can add some details to the picture of events taking place in the brain, and in existing circumstances it seemed advisable to publish what had been done.…”
mentioning
confidence: 99%